Bladder Tissue Engineering Using Biocompatible Nanofibrous Electrospun Constructs: Feasibility and Safety Investigation - Shakhssalim, Nasser; Dehghan, Mohammad Mehdi; Moghadasali, Reza; Soltani, Mohammad Hossein; Shabani, Iman; Soleimani, Masoud (Urology Journal, 2012)
Purpose: To investigate the feasibility and safety of using biocompatible, nanofibrous electrospun polycaprolactone (PCL) and combination of polylactic acid (PLLA) and PCL mats in a canine model. Materials and Methods: Plasma-treated electrospun unseeded mats were implanted in three dogs. The first dog was sacrificed after 3 months and the second and third ones after 4 months, and then, the graft was examined macroscopically with subsequent morphological and histochemical evaluation. Results: Both films showed high levels of cell infiltration and tissue formation, but body response to PLLA/PCL mat in comparison to PCL mat was very low. All three implantation models showed the same light microscopic morphology, immunohistochemistry, and scanning electron microscopy results; nevertheless, only the PCL/PLLA model showed favorable clinical results. Conclusion: Based on these data, nanofibrous PLLA/PCL scaffolding could be a suitable material for the bladder tissue engineering; however, it deserves further investigations.